Determination of post-mortem interval (PMI) via immunohistochemical localization and expression of biogenic amine (cadaverine) - Yeow, Mei Juan (2017)
A dearth of knowledge still exists despite extensive research being conducted on a reliable post mortem interval (PMI) indicator. Biogenic amine has never been attempted as an indicator of PMI and is evaluated in this study based on immunologically expressed cadaverine. Samples of the brain, liver, muscle and testis obtained from three dogs at 0, 12th, 18th, and 24th hour post-euthanasia were immediately fixed in 10% formalin and routinely processed for histology (Haematoxylin and Eosin) and cadaverine immunohistochemistry (IHC). The H&E stained samples were also subjected to morphometric analysis. Comparable cadaverine expressions found at 18th and 24th hour post-mortem were higher than 0 and 12th hour (p<0.01). Hepatic cadaverine expression surpassed other tissues, except of the brain (p<0.01). However, a time-dependent effect was found on all organs tested (p<0.01). The morphometry of hepatocytes, neurons and seminiferous tubules were significantly different (p<0.01). In conclusion, it appears that cadaverine expression may serve as a PMI indicator. However, similar studies should be subjected to different biogenic amines along with its exact quantification.